2010
DOI: 10.1007/s10762-010-9668-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Compact Sub-Terahertz Gyrotron for Spectroscopic Applications

Abstract: In this paper we present the initial design of a novel and versatile high frequency gyrotron with parameters suitable for application to various spectroscopic studies that require coherent radiation in the subterahertz frequency range (such as NMR/DNP spectroscopy, ESR spectroscopy, spectrometer based on the X-ray detected magnetic resonance etc.). The most characteristic feature of the design is that it utilises a compact, cryogen-free 8 T superconducting magnet. As a result, the overall dimensions of the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As it has already been pointed out in [1], the closest potential competitor to the operating TE 8,2 mode is the TE 0,2 mode at the fundamental of the cyclotron frequency. The simulations however have shown that this mode is suppressed by the operating mode.…”
Section: Analysis Of Mode Competitionmentioning
confidence: 81%
See 1 more Smart Citation
“…As it has already been pointed out in [1], the closest potential competitor to the operating TE 8,2 mode is the TE 0,2 mode at the fundamental of the cyclotron frequency. The simulations however have shown that this mode is suppressed by the operating mode.…”
Section: Analysis Of Mode Competitionmentioning
confidence: 81%
“…Its initial design that includes both the design of the electron-optical system (EOS) and the resonant cavity was presented in [1]. It is expected that the tube will operate at the second harmonic of the cyclotron frequency and will generate radiation in a CW regime with an output power of about 100 W and frequency tunable to up to 424 GHz, respectively.…”
mentioning
confidence: 99%
“…From the other side, it is clear that when used as radiation sources in a sophisticated laboratory environment it is easier to embed them into the rest of the equipment if their dimensions are smaller. In recent years, the availability of compact cryo-free superconducting magnets has made it possible to develop much more compact gyrotrons [18][19][20]. According to the nomenclature adopted at FIR UF, these recently developed devices are marked by the letter "C", which stands for "compact".…”
Section: Figure 1: Gyrotron Fu Cw I Equipped With a Corrugated Wavegu...mentioning
confidence: 99%
“…Bulky and heavy devices like conventional gyrotrons are not suitable for such systems. This motivated us to develop a concept of a compact gyrotron [41,42], which is based on the utilization of compact liquid He-free superconducting magnets and slim tubes with a special design allowing its insertion in the relatively small diameter bore of the solenoid. The mentioned special design envisages also development of an optimized low-voltage and low-current MIG with reduced (minimized) radial dimensions.…”
Section: Recently Developed Gyrotrons Members Of the Fu Cw C And Fu mentioning
confidence: 99%